(untitled) (Hematology Meeting Reports, 2009)
The aim of this report is to review briefly the ontogeny of hematopoiesis in mice and humans and to discuss accumulating evidence that hematopoietic stem cell activity arises from endothelial cells during embryogenesis. This overview summarizes information present in the PubMed online database and from experiments conducted in our laboratory. The major sites of hematopoiesis change throughout development in mice and humans. Hematopoietic cells are derived from mesoderm precursors within the embryo, as well as in the yolk sac, and recent evidence for direct development of blood cells from endothelium is compelling. The ontogeny of hematopoiesis is similar in mice and humans. Understanding the role of endothelium in producing blood cells may provide new strategies for augmenting hematopoiesis in patients undergoing stem cell transplantation.